Effects of Pioglitazone on Stearoyl-CoA Desaturase in Obese Zucker fa/fa Rats - Tomoaki Toyama; Naomi Kudo; Yasuhide Hibino; Atsushi Mitsumoto; Masazumi Nishikawa; Yoichi Kawashima (Elsevier, 2007)
The effects of a peroxisome proliferator activated receptor γ (PPARγ) agonist on hepatic stearoyl-CoA desaturase (SCD) in insulin-resistant and obese Zucker fa/fa rats were studied. The administration of pioglitazone, a PPARγ agonist, to Zucker obese rats greatly improved their insulin sensitivity. The treatment of Zucker obese rats with pioglitazone did not affect the index of fatty acid desaturation of either serum or liver. Hepatic SCD activity and the mRNA level of SCD1 were not changed by treatment of the rats with pioglitazone. The activity of palmitoly-CoA chain elongase, which is involved in the biosynthesis of oleic acid in concert with SCD, was not significantly altered when Zucker obese rats Received pioglitazone. Although neither the activity nor mRNA expression of acyl-CoA oxidase was changed by treatment of Zucker obese rats with pioglitazone, the mRNA expressions of both sterol regulatory element-binding protein-1c and acetyl-CoA carboxylase sensitively responded to the challenge by pioglitazone. These results suggest that the insulin sensitivity of insulin-resistant and obese Zucker fa/fa rats is improved by pioglitazone independently of SCD activity. Keywords:: pioglitazone, stearoyl-CoA desaturase, palmitoyl-CoA elongase, oleic acid